Automação do setor de cavaco da empresa Trombini Embalagens S.A. - Reis, Ronaldo Adriano dos (2013)
This work aims to automate the process on the production line Trombini chip company, with the goal of obtaining increased production and generate more time for scheduled maintenance. The Project Consist of replacing all components that are in the field and electrical panels. The industry does not work with a PLC in the MCC chip. With the controller will insert a retrofit ABB AC800M model, to be built around the PLC program. Since we added the same effect Exchange of all the matches foe the drive by chip inverters Frequency Model ACS355, to make a speed control chip process, speeding up production there. All inverters are connected there Profibus network, aiming to reduce the physical inputs and outputs used in the whole process has provided. Will also be added to IHM operator to view and control the process has provided, connect, stop and view process failures. Aiming operator ergonomics that today this is uncomfortable being built a table with all controls, monitors and IHM visualization process, to be carried out it Will be removed from the electrical panel and hydraulic unit that the operating room in order to improve space.